EFEKTIVITAS INKUIRI TERBIMBING UNTUK MENINGKATKAN KPS TERPADU PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Febry Zahara; Emmawaty Sofya; Tasviri Efkar (Universitas Lampung, 2019)
The aim of this research was to describe the effectiveness of guided inquiry learning model to the integrated process science skills of electrolyte and non electrolyte solution material. The population of this study was all of classes X MIA in one of the high schools in Natar, while the sample of this study was class X MIA 2 and X MIA 3, this research used Quasi Experimental method with Pretest-Posttest Control Group Design. The results showed that the average n-Gain value of the experiment class was higher than the control class, with a large measure of influence. The results showed that learning with guided inquiry models is effective for increasing students' integrated proces secience skill on electrolyte and non electrolyte solution matery. Keywords: guided inquiry, electrolyte and non electrolyte solutions, integrated process science skills. Penelitian ini bertujuan untuk mendeskripsikan keefektivan model pembelajaran inkuiri terbimbing untuk meningkatkan keterampilan proses sains terpadu materi larutan elektrolit dan non elektrolit. Populasi penelitian ini adalah seluruh kelas X MIA di salah satu SMA di Natar, sedangkan sampel penelitian ini adalah kelas X MIA 2 dan X MIA 3, menggunakan metode Quasi Eksperimendengan Pretest-Posttest Control Group Design. Hasil penelitian menujukkan rata-rata nilai n-Gain kelas eksperimen lebih tinggi daripada kelas kontrol, dengan ukuran pengaruh yang besar. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa pembelajaran dengan model inkuiri terbimbing efektif untuk meningkatkan KPS terpadu siswa pada materi larutan elektrolit dan non elektrolit.Kata kunci: inkuiri terbimbing, larutan elektrolit dan non elektrolit, KPS terpadu.